REVIEW OF PSYCHOANALYSIS IN CHARACTER FORMATION IN FIFTH SEMESTER STUDENTS OF THE DEPARTMENT OF ENGLISH LITERATURE, BALIKPAPAN UNIVERSITY - Ningsih, Era Wahyu (Prologue: Journal on Language and Literature, 2024)
This study examines the influence of childhood experiences on the character development of fifth-semester English Literature students at Universitas Ba-likpapan through a psychoanalytic perspective. Utilizing qualitative meth-ods, including surveys and interviews, the research explores how early life experiences, internal conflicts, and academic environments shape students' social interactions and decision-making processes. The findings indicate that 65.6% of respondents feel their childhood experiences significantly affect their current social interactions, aligning with Sigmund Freud's theory that early developmental stages impact adult personality. Additionally, 34.4% of student’s report that past emotional experiences influence their ability to face academic challenges, highlighting the role of the id, ego, and superego in managing internal conflicts. The study underscores the importance of pos-itive interactions with educators in reinforcing moral values and shaping student character, suggesting that higher education should not only focus on academic knowledge but also support holistic character development. The implications for educators include creating an environment conducive to fostering students' emotional resilience and integrity.